Pengaruh Motivasi Investasi dan Pengetahuan Investasi terhadap Minat Investasi di Pasar Modal pada Mahasiswa Politeknik Negeri Medan (Jurnal Ekonomi Bisnis dan Akuntansi, 2025)
This study aims to analyze the effect of investment motivation and investment knowledge on students’ interest in investing in the capital market. The background of this research is driven by the increasing importance of young generations, particularly university students, as potential investors who play a significant role in supporting the development of the Indonesian capital market. The research employed a quantitative approach using a survey method by distributing structured questionnaires to 300 students of Politeknik Negeri Medan. The sample was selected through cluster random sampling to obtain a representative dataset. The collected data were analyzed using multiple linear regression with the assistance of IBM SPSS version 29, after conducting validity tests, reliability tests, and classical assumption tests to ensure the quality and feasibility of the research instrument. The results indicate that both investment motivation and investment knowledge have a positive and significant influence on students’ interest in investing in the capital market. These findings highlight that the higher the level of motivation and understanding of investment instruments, particularly stocks, the greater the tendency of students to participate in investment activities. The implication of this research is the importance of enhancing capital market literacy among students through targeted education, training, and socialization programs to encourage the growth of young investors who are more knowledgeable, aware, and wise in making investment decisions.